Study of gas cell stability during breadmaking using x-ray microtomography and dough rheology - Pickett, Melissa M. (Kansas State University, 2009)
Viscoelastic wheat flour doughs are renowned for their ability to produce high quality aerated bread products. Dough exhibits extremely complex rheological properties which makes it capable of occluding and retaining gas cells. The ability of these bubbles to resist failure and remain stable throughout the proofing and baking process is critical to final bread structure and volume. Understanding these factors is important when creating the distinct structural and textural characteristics that consumers desire in baked products. In this study, a method was established for using X-ray microtomography (XMT) to study the microstructure of proving dough as well as bread made from three very different wheat flours. Doughs were prepared according to AACC Method 10-10B optimized straight-dough bread-making method. Sections from unproofed (0 min), underproofed (20 min) and optimally proofed (40 min) doughs were carefully cut and frozen at –80°C. Baked loaves were also prepared following standard test bake procedures. Small specimens were cut from two locations of both the proofed and baked loaves prior to microstructural analysis. A total of 96 dough and bread samples were scanned using a high resolution desktop X-ray micro-CT system Skyscan1072 (Skyscan, Belgium) consisting of an X-ray tube, an X-ray detector and a CCD-camera. X-ray images were obtained from 137 rotation views through 180° of rotation. Hundreds of reconstructed cross sectional images were analyzed using CTAn (v.1.7) software. 3-D analysis of the bubbles indicated that average dough void fractions increased dramatically over proof time from 30.9% for the unproofed dough (0 min) to 62.0% and 74.5 % for the underproofed (20 min) and optimally proofed (40 min) doughs respectively. Oven spring caused further expansion in the baked loaves which increased average void fraction to 84.3%. Gas cell size distributions were largely skewed to the right and shifted in that same direction as processing time increased. Differences in gas cell size seen among flour varieties were largely due to variations in the size of the largest cells caused by coalescence.
Keywords: X-ray microtomography; Dough microstructure; Microstructure; Bread microstructure; Agriculture, Agronomy (0285); Agriculture, Food Science and Technology (0359)